ANALISIS MARGIN DAN KEUNTUNGAN PEDAGANG PENGECER IKAN LAUT DI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Risvaldi Milianto Pali; Ludia T. Wambrauw; Mori Muzendi, Agustina Sylvanie (Sosio Agri Papua, 2025)
The marketing of marine fish in Manokwari Regency involves various actors, including fishermen, collectors, and retailers. Marketing activities are carried out not only in central fish markets but also at roadside huts along major thoroughfares in busy commercial areas or residential neighborhoods. The selection of selling locations and the marketing strategies employed by traders significantly influence the margins and profitability of their businesses. This study aims to: (1) analyze the marketing margins received by traders based on fish species in the Arfai Area of Manokwari Regency; and (2) evaluate the marketing profitability of roadside cottage traders in Arfai based on the type of fish sold. This research utilizes a survey method with both quantitative and qualitative approaches. Respondents were selected through purposive sampling, focusing on fish retailers who do not also act as fishermen or wholesale traders. The study covers five primary fish species: skipjack, tuna, cob, yellowtail scad (oci), and snapper. The results indicate that the marketing margins range from Rp. 23,304/Kg to Rp. 41,660/Kg, with an average margin of Rp. 31,061/Kg across all fish types. In terms of profitability, traders selling fish at roadside huts reported profits ranging from Rp. 2,761/Kg to Rp. 21,520/Kg, with an average profit of Rp. 12,024/Kg. Among the analyzed fish species, oci yielded the highest profit margin, while skipjack exhibited the lowest profitability. These findings offer valuable insights into the marketing dynamics of marine fish in Manokwari, highlighting key factors affecting profitability and distribution efficiency. Understanding these elements can help develop strategic marketing approaches that enhance traders' earnings and contribute to the economic sustainability of local fish markets.